Topic Specificity and Antecedents for Preservice Biology Teachers’ Anticipated Enjoyment for Teaching About Socioscientific Issues: Investigating Universal Values and Psychological Distance - Büssing, Alexander Georg; Dupont, Jacqueline; Menzel, Susanne (Frontiers in Psychology, 2020)
Enjoyment for teaching represents one of the most frequently reported teaching emotions and positively affects student outcomes. Therefore, researchers and teacher educators need to understand its nature and underlying appraisal processes to prepare motivated teachers in initial teacher education. Using cross-sectional questionnaire data from 189 German biology pre-service teachers (73.5 % female, Mage = 23.45 years, SDage = 3.71) we empirically tested the topic-specific structure and antecedents of the participants’ anticipated enjoyment for teaching. We adapted the established teacher emotion scales (TES) to measure pre-service teachers’ trait-based enjoyment for teaching by reframing the items with the environmental socio-scientific issues of returning wolves and climate change, and the health socio-scientific issue of pre-implantation genetic diagnosis. Confirmatory factor analysis (CFA) confirmed the best fit of a topic specific model. We also found different correlations for the anticipated enjoyment for teaching about the issues, but no significant mean differences. Concerning further topic-specific antecedents, the environmentally oriented universal value of universalism predicted the anticipated enjoyment for teaching about returning wolves and the socially oriented universal value of benevolence predicted the anticipated enjoyment for teaching about pre-implantation genetic diagnosis. Both values inconsistently predicted the anticipated enjoyment for teaching about climate change. While this is in line with the complex nature of this socio-scientific issue, psychological distance was a predictor for the anticipated enjoyment for teaching about every topic. While these effects remained stable when controlling for demographic variables, male participants showed a higher anticipated enjoyment for teaching about wolves and climate change, and female pre-service teachers for teaching about pre-implantation genetic diagnosis. Further studies are needed to investigate if the results can be transferred to in-service teachers or to other teaching emotions. Furthermore, future studies could examine effects on other factors relevant for teaching emotions such reactions to student behavior, which have been described as central for the causation of teaching emotions in prior studies (i.e. ‘reciprocal model of teaching emotions’). The present study stimulates such new studies and adds important knowledge to the understanding of topic specificity and topic-specific antecedents of anticipated enjoyment for teaching, which are relevant for teacher education and professional development.